Motivasi Kebutuhan Dasar Tokoh Dalam Novel Perempuan Yang Menangis Kepada Bulan Hitam Karya Dian Purnomo: Tinjauan Psikologi Sastra Abraham Maslow - Yoyong Yoyong; Lazarus Linarto; Linggua Sanjaya Usop; Alifiah Nurachmana; Lestari Lestari; Lusyanae Lusyanae (Universitas Palan, 2023)
This research aims to describe the five basic needs fulfillment according to Abraham Maslow's theory, namely fulfilling basic physiological needs, fulfilling the need for security, fulfilling the need for love of belonging, fulfilling the need for self-esteem, and finally fulfilling the need for self-actualization. This research is qualitative descriptive research. This data collection technique is carried out by reading, listening and taking notes. The data analysis techniques used in this research are data collection, data reduction, data presentation, and the final step is drawing conclusions. The theory used in this research is Abraham Maslow's basic needs motivation theory, with a review of psychological literature. The data source in this research is the novel entitled Women Who Cry to the Black Moon by Dian Purnomo. Based on the study and discussion of the research results, it can be concluded that the main character in the novel Wanita Yang Cried to the Black Moon by Dian Purnomo can fulfill all her basic needs. (1) Motivation to fulfill basic physiological needs appeared in 25 data, which included the need to eat and drink, the need for clothing, the need for rest, the need for shelter and the need for air. (2) Motivation to fulfill the need for security appeared in 27 data. (3) Motivation to fulfill the need for love and belonging appeared in 25 data. (4) Motivation to fulfill the need for self-esteem appeared in 13 data. (5) Motivation to fulfill self-actualization needs appeared in 14 data.